Evaluation of the auditory brainstem response test in patients with type 2 diabetes mellitus - Mahbubeh Sheikhzadeh; Fereshteh Bagheri; Mohammad Ali Bayani; Milad kami; Mohsen Monadi (Babol University of Medical Sciences, 2024)
Background: Hearing loss is an unknown complication of diabetes mellitus(DM). The aim of this study was to evaluate hearing function using auditory brainstem response (ABR) in diabetes patients. Methods: The present case-control study was performed on thirty diabetic patients as a case group and thirty healthy individuals as a control group. Baseline demographic information, HbA1c level, and duration of diabetes were obtained from all diabetic patients. In all subjects, the ABR and pure-tone audiometry (PTA) tests were performed and the results were analyzed using the t-test and logistic regression. Results: The absolute latency of I was significantly lower in diabetes patients. The absolute latency of III and the interpeak latencies (IPL) I-III were significantly higher in diabetic patients. No significant relationship was noticed in the absolute latency of V and the IPL I-V among diabetic patients in the right and left ears (P>0.05). Conclusion: The results of this study suggested that diabetes may cause central auditory dysfunction manifested on the absolute latency of III, the IPL I-III and III-V.